2018
DOI: 10.1016/j.jclepro.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the environmental benefits of remanufactured products: Method and application

Abstract: Although the importance of reusing products has been stated frequently, both in legislation and by academics, the scientific literature does not provide comprehensive and systematic methods of assessing the reuse of a generic product from an environmental point of view. Moreover, the definitions of reuse provided in the literature and legislation are not always consistent. This article introduces an original classification of different types of reuse, including some suggested definitions. It then focuses on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…The LCA method's shortcomings were also addressed. Ardente et al [135] utilized an LCA approach to assessing the environmental benefits of remanufacturing. A server was selected as a case-study product; it was reported that even though the remanufactured product consumes more energy for running, it is still environmentally beneficial.…”
Section: Other Methods and Studiesmentioning
confidence: 99%
“…The LCA method's shortcomings were also addressed. Ardente et al [135] utilized an LCA approach to assessing the environmental benefits of remanufacturing. A server was selected as a case-study product; it was reported that even though the remanufactured product consumes more energy for running, it is still environmentally beneficial.…”
Section: Other Methods and Studiesmentioning
confidence: 99%
“…The GWP impact analysis refers to the international life cycle data system (International Reference Life Cycle Data System, 2010). The basic scenario is set as the GWP impact of a new engine (average weight 245 kg) produced during the life cycle (Ardente et al, 2018).…”
Section: Recycling Of Elvs Materials Chinamentioning
confidence: 99%
“…It has been distinguished the following recovery forms in accordance with the point of reentry in the value chain: Reuse, repair, restoration, remanufacture, cannibalization, recycling, energy recovery, and garbage dumps [36]. More recently, It was also identified remanufacturing, repair and recycling as product recovery options, and later, some different types of reuse have been defined [37,38].…”
Section: Product Recoverymentioning
confidence: 99%
“…Effective product returns and safe product relocation/disposal can reduce environmental harm and economic loss. Therefore, remanufacturing products have potential environmental benefits [38] and help industry to fall in line with sustainability objectives [2].…”
Section: Disassembly and Remanufacturing Managementmentioning
confidence: 99%
See 1 more Smart Citation